Hubungan Self Efficacy dengan Kemampuan Berpikir Positif pada Remaja di SMP Karya Bhakti Kecamatan Tarabintang Kabupaten Humbang Hasundutan Tahun 2021 - Elisabeth Christina Tumanggor; Lindawati Simorangkir; Amnita Ginting (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Self efficacy is someone who has high confidence where individuals are able to direct behavior to be active and more diligent with all academic activities. Positive ability to reason is a disposition or conduct that is possessed to have the option to settle on decisions by utilizing a solid and clear psyche that starts or emerges from positive energy and furthermore sees everything with regards to its decency. This study expects to decide if there is a connection between self-viability and positive ability to reason. The exploration strategy utilized is connection with cross sectional methodology, the quantity of respondents is 53 individuals. This retrieval techniqueiis done by using questionnaires that are distributed directly. Sampling using simple random sampling with aitotal of 53 respondents. Their results showed that most of the respondents with High Self Efficacy were 43 people (81.1%) with the ability to think positively in the high category as many as 25 people (47.2%). Thelr results of the Fisher's Exact Test correlation test with a p-value of 0.488 (p <0.05) means that there is no significant relationship between self-efficacy and the ability to think positively in adolescents at Karya Bhakti Junior High School, Tarabintang District, Humbang Hasundutan Regency. The conclusion is that the self-efficacy of Karya Bhakti Junior High School students is very high, while students who have very low positive thinking skills are expected to be better able to change attitudes or behavior to improve their ability to think positively and apply self-efficacy in each individual.